Krisis Otoritas Keilmuan di Era Digital: Perspektif Qur’ani terhadap Fenomena The Death of Expertise - Maudy Muzalifah Azzahra; Bashori (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The development of digital technology has significantly transformed the dissemination of knowledge in society. Besides providing easier access to information, this condition has also given rise to the phenomenon of the death of expertise, namely the weakening of scientific authority due to the dominance of popularity and the rapid flow of digital information. This phenomenon causes people to rely on viral figures as sources of knowledge without considering their validity and scientific competence. This study aims to examine the phenomenon of the death of expertise and formulate efforts to reconstruct scientific authority based on Qur’anic values. This research employs a qualitative method with a library research approach using thematic interpretation (maudhu’i). The findings indicate that the death of expertise leads to several issues, including the decline of scientific authority, the spread of unverified knowledge, and the emergence of superficial understanding. The reconstruction of scientific authority can be pursued through collaboration among knowledge communities, strengthening the culture of tabayyun (verification), and optimizing digital media based on knowledge validity.